Transient Gene Expression as a Tool to Monitor and Manipulate the Levels of Acidic Phospholipids in Plant Cells - Noack, Lise C; Pejchar, Přemysl; Sekereš, Juraj; Jaillais, Yvon; Potocký, Martin (Methods in molecular biology (Clifton, N.J.), 2019)
Anionic phospholipids represent only minor fraction of cell membranes lipids but they are critically important for many membrane-related processes, including membrane identity, charge, shape, the generation of second messengers, and the recruitment of peripheral proteins. The main anionic phospholipids of the plasma membrane are phosphoinositides phosphatidylinositol 4-phosphate (PI4P), phosphatidylinositol 4,5-bisphosphate (PI4,5P2), phosphatidylserine (PS), and phosphatidic acid (PA). Recent insights in the understanding of the nature of protein-phospholipid interactions enabled the design of genetically encoded fluorescent molecular probes that can interact with various phospholipids in a specific manner allowing their imaging in live cells. Here, we describe the use of transiently transformed plant cells to study phospholipid-dependent membrane recruitment.
Keywords: Transient expression; Pollen tube; exprese genu; Gene Expression; Fluorescent Dyes; konfokální mikroskopie; fluorescenční mikroskopie; Microscopy; transformace genetická; pyl; Nicotiana benthamiana; Microscopy, Confocal; luminescentní proteiny; Transformation, Genetic; Pollen; rostlinné buňky; Microscopy, Fluorescence; Nicotiana; Phospholipids; Nicotiana tabacum; Phosphatidylinositols; Phosphoinositides; Phospholipid-binding domains; Plant Cells; fluorescenční barviva; fosfolipidy; Luminescent Proteins; fosfatidylinositoly; tabák